Melomics: A Case-Study of AI in Spain - Sánchez-Quintana, Carlos Alberto; Moreno-Arcas, Francisco; Albarracín Molina, David Daniel; Fernández-Rodríguez, Jose David; Vico-Vela, Francisco José (Association for the Advancement of Artificial Intelligence, 2013)
Traditionally focused on good old-fashioned AI and robotics, the Spanish AI community holds a vigorous computational intelligence substrate. Neuromorphic, evolutionary, or fuzzylike systems have been developed by many research groups in the Spanish computer sciences. It is no surprise, then, that these naturegrounded efforts start to emerge, enriching the AI catalogue of research projects and publications and, eventually, leading to new directions of basic or applied research. In this article, we review the contribution of Melomics in computational creativity.
Keywords: Inteligencia artificial; Algorithmic composition; Artificial intelligence